2021
DOI: 10.24940/theijhss/2021/v9/i5/hs2105-030
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Medical Camps in Ensuring Equity in Accessing Health Care Services in Kenya

Abstract: This study was carried out to help improve the management and organization of the medical camps in Kenya by the various key stakeholders thus enabling the medical camps achieve the overall goal of enabling access of quality affordable health care services to the disadvantaged and marginalized population in Kenya in acknowledgement that equity in the accessing and provision of health care services is an underlying principle intertwined in the human rights principles. Everyone irrespective of their social and ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Through these camps, people can be educated on aspects like how and what to eat and drink, how and how long should they sleep, healthy recreational habits, and when to seek medical attention. Since most of the time medical services provided during these camps are free, studies have shown that such healthcare camps ensure equity in accessing health care services including the availability of health education to the community [19][20][21][22] . Medical students can do this by organizing, implementing, or participating in such events through their local students' professional associations like the International Federation of Medical Students' Association (IFMSA) or their medical schools [23,24] .…”
Section: Role Of Medical Students In Community Lifestyle Transformationmentioning
confidence: 99%
“…Through these camps, people can be educated on aspects like how and what to eat and drink, how and how long should they sleep, healthy recreational habits, and when to seek medical attention. Since most of the time medical services provided during these camps are free, studies have shown that such healthcare camps ensure equity in accessing health care services including the availability of health education to the community [19][20][21][22] . Medical students can do this by organizing, implementing, or participating in such events through their local students' professional associations like the International Federation of Medical Students' Association (IFMSA) or their medical schools [23,24] .…”
Section: Role Of Medical Students In Community Lifestyle Transformationmentioning
confidence: 99%